From Sound to Movement: Mapping the Neural Mechanisms of Auditory–Motor Entrainment and Synchronization - Marija Pranjić; Thenille Braun Janzen; Nikolina Vukšić; Michael Thaut (Brain Sciences)
Background: Humans exhibit a remarkable ability to synchronize their actions with external auditory stimuli through a process called auditory–motor or rhythmic entrainment. Positive effects of rhythmic entrainment have been demonstrated in adults with neurological movement disorders, yet the neural substrates supporting the transformation of auditory input into timed rhythmic motor outputs are not fully understood. We aimed to systematically map and synthesize the research on the neural correlates of auditory–motor entrainment and synchronization. Methods: Following the PRISMA-ScR guidelines for scoping reviews, a systematic search was conducted across four databases (MEDLINE, Embase, PsycInfo, and Scopus) for articles published between 2013 and 2023. Results: From an initial return of 1430 records, 22 studies met the inclusion criteria and were synthesized based on the neuroimaging modality. There is converging evidence that auditory–motor synchronization engages bilateral cortical and subcortical networks, including the supplementary motor area, premotor cortex, ventrolateral prefrontal cortex, basal ganglia, and cerebellum. Specifically, the supplementary motor area and the basal ganglia are essential for beat-based timing and internally guided rhythmic movements, while the cerebellum plays an important role in tracking and processing complex rhythmic patterns and synchronizing to the external beat. Self-paced tapping is associated with additional activations in the prefrontal cortex and the basal ganglia, suggesting that tapping in the absence of auditory cues requires more neural resources. Lastly, existing studies indicate that movement rate and the type of music further modulate the EEG power in the alpha and beta frequency bands. Conclusions: These findings are discussed in the context of clinical implications and rhythm-based therapies.